2014
DOI: 10.3906/biy-1401-47
|View full text |Cite
|
Sign up to set email alerts
|

Squalestatin-induced production of taxol and baccatin in cell suspension culture of yew (Taxus baccata L.)

Abstract: Various elicitors have already been reported to enhance the production of taxol and related taxanes. In this study, effects of a fungal metabolite, squalestatin, on production of taxol and baccatin III were studied. Expressions of 4 key involved genes, ts, dbat, bapt, and dbtnbt, in suspension cultures of Taxus baccata were also detected using qPCR. Results showed that application of squalestatin significantly increased taxol and baccatin III yields. Increased expressions of the genes were in accordance with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Hence, we propose that subsequent retrograde redox signals, rather than chloroplast ROS per se , may act on MdMIR156 transcription. During phase change in apple, the contents of H 2 O 2 and GSH varied significantly within a considerable extent, in chemically-treated apple in vitro shoots, concentrations of H 2 O 2 and GSH changed drastically, even to an extreme level 10 , 65 , 66 , 67 . But in all cases, miR156 levels varied with GSH concentration and GSH/GSSG ratio but not directly with H 2 O 2 concentration 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we propose that subsequent retrograde redox signals, rather than chloroplast ROS per se , may act on MdMIR156 transcription. During phase change in apple, the contents of H 2 O 2 and GSH varied significantly within a considerable extent, in chemically-treated apple in vitro shoots, concentrations of H 2 O 2 and GSH changed drastically, even to an extreme level 10 , 65 , 66 , 67 . But in all cases, miR156 levels varied with GSH concentration and GSH/GSSG ratio but not directly with H 2 O 2 concentration 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Isoprenoids and sterols were utilized as substrates for the accumulation of taxanes [20]. The increase in production of taxol or their intermediate baccatin III might be due to the effect of SQase on the gene expression at the initial step in the isoprenoid pathway [20]. These sterols are synthesized from mevalonic acid via the isoprenoid pathway [58].…”
Section: Resultsmentioning
confidence: 99%
“…Supplementation of sterol biosynthesis inhibitors such as tebuconazole and triadimefon in the culture medium showed increased yield of fungal taxol [19]. Amini et al [20] reported that squalestatin induced accumulation of H 2 O 2 and endogenous methyl jasmonate (MeJ) but suppressed squalene synthase (SQase) activity. These were correlated with the overexpression of key genes, resulting in remarkable increase in taxane production.…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, the most effective components of medical plants are secondary metabolites and elicitation of plant cells in culture represents a useful biotechnological tool to improve the production of these valuable metabolites. Therefore, the application of fungal elicitors largely solvesthe problem of low amounts of the active ingredients such as, the application of squalestatin significantly increasestaxol and baccatin III yields in cell suspension culture of yew (Taxus baccata L.) (Amini et al 2014). However, not all the fungal are useful and suited to the production of secondary metabolites, some pathogenic fungal cause cell hypersensitive responses and programed cell death, but non-pathogenic fungal may either cause general defense responses or no response.…”
Section: Discussionmentioning
confidence: 99%